2002
DOI: 10.1021/la010803f
|View full text |Cite
|
Sign up to set email alerts
|

Final Phase of Alkanethiol Self-Assembled Monolayers on Au(111)

Abstract: Time-dependent phase transitions of closely packed alkanethiol self-assembled monolayers (SAMs) on Au(111) were investigated by scanning tunneling microscopy (STM). We report a new phase, the 6 × √3 superlattice, that exhibits deviations from the hexagonal packing arrangement formed through long-term rearrangement of the usual c(4 × 2) superlattice of alkanethiol SAMs. Our STM images show clearly systematic phase transitions with molecular-scale images from the c(4 × 2) phase to the 6 × √3 phase. This result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
105
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 33 publications
5
105
0
Order By: Relevance
“…Adsorption states, molecular structures, growth processes, and electronic structures of alkanethiol (AT) SAMs on gold have been extensively investigated using various surface characterization techniques. [4][5][6][7][8][9] The introduction of functional groups to the tail of the sulfur headgroup may be useful in future applications to organic electronic devices. For example, the use of a π-conjugated tail group is very simple and convenient method for obtaining functionality in organic electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption states, molecular structures, growth processes, and electronic structures of alkanethiol (AT) SAMs on gold have been extensively investigated using various surface characterization techniques. [4][5][6][7][8][9] The introduction of functional groups to the tail of the sulfur headgroup may be useful in future applications to organic electronic devices. For example, the use of a π-conjugated tail group is very simple and convenient method for obtaining functionality in organic electronics.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In particular, the formation and structure of alkanethiol SAMs on gold surfaces have been extensively studied using various surface characterization techniques. [6][7][8][9] Experimental conditions, such as solvent, temperature, concentration, immersion time, and substrate cleanliness significantly affect the formation and structure of alkanethiol SAMs. 1,[6][7][8][9] Among them, solvent choice is a very important factor for determining the structural quality and formation kinetics of SAMs.…”
mentioning
confidence: 99%
“…[6][7][8][9] Experimental conditions, such as solvent, temperature, concentration, immersion time, and substrate cleanliness significantly affect the formation and structure of alkanethiol SAMs. 1,[6][7][8][9] Among them, solvent choice is a very important factor for determining the structural quality and formation kinetics of SAMs. [10][11][12][13][14][15][16][17][18] Ellipsometry measurements have shown that the solvent, including ethanol, N,N'-dimethylformamide (DMF), toluene, hexadecane, and cyclooctane, had no effect on the thickness of hexadecanethiol SAMs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,6,7,10 Several different two-dimensional (2D) phases were observed depending on the surface coverage and preparation conditions. 3,5 2D SAMs were formed by a delicate balance between sulfur atom-gold substrate interaction and molecule-molecule interaction. 1 In particular, the backbone structures of organic thiols strongly affect the structural order and 2D packing structures of SAMs.…”
Section: -10mentioning
confidence: 99%